ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK DI MTS AL- WASHLIYAH SEI MENCIRIM - Nanda Elika Rahim; Muliawan Firdaus (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The background of this research was class VIII MTs Al Washliyah Sei Mencirim with learning difficulties in following the teaching of mathematics with a scientific approach introduced by Kemendikbud in Curriculum 2013. Such problems made researchers interested in conducting further research. The purpose of this study to determined the cause of students experiencing difficulties in the learning process of mathematics with a scientific approach. This research was a quantitative and qualitative research. Data obtained by observation, questionnaires, and interviews. The research instrument used was a questionnaire teachers and students, learning and activity observation sheet of students in the classroom, as well as interview guides teachers and students. The results showed that the form of learning difficulties for class VIII students that appeared in mathematics learning on flat sided space material with a scientific approach were students having difficulty understanding and solving flat sided space problems, difficulty in asking flat sided shape problems, difficulty in trying to solve problems. in the form of reasoning and difficulties in concluding the material that has been studied. The cause of the emergence of learning difficulties in mathematics learning material relations and presenting the relation with the approach of scientific because of the difficulties caused by teachers such as: (1) the teacher wasn’t directing students to ask and concluded, (2) teachers didn’t prepare the implementation stages observe well with the acquisition of a percentage 40%, (3) the issue of the reasoning given fairly difficult, (4) lack of skills and understanding of teachers in implementing the learning process with the approach of the scientific with the acquisition of a percentage of 40% and the difficulties that arise from the students themselves, such as: (1) lack of awareness of students to learn and willing to follow the learning process, (2) the fear that a dominant appears, (3) students experience language impairments, (4) students impaired recall, (5) students impaired reasoning.